PB (at) GOx (at) ZIF-8 material, preparation method thereof and application of PB (at) GOx (at) ZIF-8 material in biosensor
Through the PB@GOx@ZIF-8 material combined with PB and ZIF-8, the stability and sensitivity problems of the non-invasive blood glucose detection device are solved, and high stability and high sensitivity glucose detection is achieved, which is suitable for portable sweat glucose sensors.
Patent Information
- Application Number
- CN202510619342.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-08-19
AI Technical Summary
The existing non-invasive blood glucose detection devices have minimally invasive use costs, inconvenient portability, and are susceptible to environmental impact. The introduction of ZIF-n materials leads to a decrease in electron conduction efficiency, affecting the sensitivity of glucose detection.
Using PB@GOx@ZIF-8 material, by combining PB and ZIF-8, the electromagnetic properties and catalytic capabilities of PB are used to maintain the activity of GOx at different temperatures, and long-term preservation is achieved in aqueous solution, while rapidly conducting and diffusing electrons generated by catalytic reactions.
High stability and high sensitivity glucose detection are achieved. The sensor can still maintain 55% activity at 100℃, and it is still effective for two months of long-term storage. The sensor can detect glucose concentration up to 1μM, providing a simple and portable biosensing method.
Smart Images

Figure CN120505304A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biosensors, and more particularly to a PB@GOx@ZIF-8 material, a preparation method thereof, and an application in biosensors. Background Art
[0002] Diabetes is a global chronic disease that threatens human life and health, and is a hot and difficult issue today. Currently, mainstream continuous blood glucose monitors on the market include those from Abbott, MiniMed, and Dexcom in the United States. These devices require the long-term implantation of microneedles subcutaneously to monitor glucose concentrations in interstitial fluid, enabling continuous blood glucose monitoring. However, these minimally invasive microneedles are expensive to process and inconvenient to carry. Furthermore, over time, they can cause small areas of skin damage or pain. More importantly, implantable sensors are susceptible to the complex environment of the receptor, resulting in inaccurate measurement results. However, the glucose concentration in human sweat is positively correlated with blood glucose concentration. By measuring sweat glucose concentration to infer blood glucose concentration, diabetic patients can be monitored quickly and easily. Therefore, non-invasive blood glucose testing is expected to provide a highly accurate, convenient, and rapid method for dynamic health assessment for diabetic patients.
[0003] In recent years, non-invasive wearable and portable devices that detect glucose in diabetic patients have been developing rapidly. These devices primarily utilize glucose oxidase (GOx). GOx catalyzes biological reactions to produce corresponding anions, cations, or electrons, which in turn generate current changes. This current change or colorimetric analysis can be used to calculate the rate of the enzymatic reaction or the strength of the enzyme activity. However, the catalytic performance of GOx is easily affected by temperature, pH, the organic system, and long-term degradation / denaturation.
[0004] In order to improve the stability of the enzyme for long-term storage and detection, the researchers introduced the zeolitic imidazolate framework (ZIF-n) structure. ZIF-n has the characteristics of high stability and high porosity. There are hydrogen bonds and van der Waals forces between its chemical bonds, so GOx can be adsorbed inside the pores. The rigid molecular structure of ZIF-n forms a protective layer around the enzyme, protecting it from the influence of the external environment and preventing degradation caused by temperature, solvents and protein hydrolysates.
[0005] However, the introduction of ZIF-n materials significantly reduces electron conduction efficiency and hinders the diffusion of electrons generated by the catalytic reaction. This reduces the rate of electrochemical detection and affects the sensitivity of glucose detection. Therefore, how to provide a highly stable and sensitive biosensor for glucose detection is an urgent problem to be solved by those skilled in the art. Summary of the Invention
[0006] In view of this, the present invention provides a PB@GOx@ZIF-8 material, a preparation method thereof, and an application in a biosensor. PB, GOx, and ZIF-8 are combined by a hydration method. By utilizing the excellent electromagnetic properties and catalytic ability of PB, the activity of GOx at different temperatures can be maintained, and it can also be preserved for a long time in ordinary environments and aqueous solutions without affecting its catalytic activity. At the same time, it can quickly conduct and diffuse the electrons generated by the GOx-catalyzed glucose reaction.
[0007] Its working principle is: in the process of catalyzing glucose, GOx acts as a catalyst, and under aerobic conditions, the reaction produces gluconic acid and hydrogen peroxide H2O2, while electrons are generated during the reaction. Then, H2O2 reacts with PB to produce Prussian white and OH - .
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] First, a preparation method of PB@GOx@ZIF-8 material is provided, which specifically includes the following steps:
[0010] S1, Preparation of PB particles
[0011] Mix potassium ferrocyanide solution, potassium chloride solution and hydrochloric acid evenly and mark it as solution A;
[0012] Thoroughly mix the ferric chloride solution, potassium chloride solution, and hydrochloric acid and mark it as solution B;
[0013] Use a microsyringe pump to simultaneously add solution A and solution B to deionized water and continue stirring at room temperature. After the titration is completed, a blue solution of PB is obtained. Then, centrifuge and wash until neutral, and dry to obtain PB powder.
[0014] Its beneficial effect is that PB is a metal hexacyanoferrate with the molecular formula Fe III 4[Fe II (CN)6]3, a molecular magnet, has low skeleton density, relatively high specific surface area, good chemical stability, and superior electrical conductivity. PB is also a peroxidase analog, capable of participating in the oxidation and reduction reactions of H2O2, and PB materials have good response and high sensitivity.
[0015] S2, Preparation of PB@GOx@ZIF-8 Materials
[0016] Prepare PB solution, mix it with glucose oxidase solution, 2-methylimidazole, and ethanol solution, and perform ultrasonic treatment to obtain solution C;
[0017] Dissolve zinc nitrate hexahydrate in ethanol solution and ultrasonicate to obtain solution D;
[0018] Finally, liquid C and liquid D were slowly mixed and reacted on a shaker, centrifuged and washed, and the resulting precipitate was frozen in liquid nitrogen and dried in a freeze dryer to obtain PB@GOx@ZIF-8 material, which was stored at -20°C for future use.
[0019] The beneficial effect lies in the fact that the PB@GOx@ZIF-8 material prepared in this invention can contain GOx within the nanocage imidazole molecular sieve framework of ZIF-8. This nanomaterial has high heat resistance, high catalytic activity, and high stability. The flexible imidazole-based imidazole molecular sieve framework and the rigid molecular structure of ZIF-8 form a protective layer around GOx, shielding the enzyme from the external environment. This prevents degradation caused by temperature, solvents, and proteolytic agents. Furthermore, the peroxide in the PB material has enzyme-like properties, forming a cascade reaction and enhancing the rate of electron diffusion.
[0020] In step S1, the concentration of potassium ferrocyanide in solution A is required to be 0.001-0.1 mol / L, the concentration of potassium chloride is required to be 0.01-1 mol / L, and the concentration of hydrochloric acid is required to be 0.01-1 mol / L;
[0021] The concentration of ferric chloride in solution B is required to be 0.001~0.1 mol / L, the concentration of potassium chloride is required to be 0.01~1 mol / L, and the concentration of hydrochloric acid is required to be 0.01~1 mol / L.
[0022] The volume ratio of solution A, solution B and deionized water in the titration is 1:1:2.5-50;
[0023] Titration speed is 100-1000 μL / min;
[0024] The rotation speed of the centrifugal washing is 5000-15000 rpm;
[0025] The drying temperature is 65°C.
[0026] In step S2, when preparing solution C, the concentration of the PB solution is 0.1 to 5 mg / mL, and the amount used is 50 to 500 μL; the concentration of the glucose oxidase solution is 1 to 10 mg / mL, and the amount used is 50 to 200 μL; the amount of 2-methylimidazole is 0.5 to 2 g; the ethanol solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 5 to 20:1, and the amount used is 5 to 20 mL; and the ultrasonic treatment time is 5 to 30 min.
[0027] When preparing solution D, the amount of zinc nitrate hexahydrate used is 10-40 mg, the ethanol solution is a mixed solution of deionized water and anhydrous ethanol, mixed in a volume ratio of 5-20:1, and the amount used is 5-20 mL; the ultrasonic treatment time is 5-10 minutes.
[0028] In step S2, solution C and solution D are slowly mixed on a shaker for a reaction time of 20 to 1440 minutes;
[0029] The rotation speed of the centrifugal washing is 2000-8000 rpm;
[0030] The liquid nitrogen freezing time is 1 to 10 minutes;
[0031] The temperature of the freeze dryer is -60°C and the time is 12 to 48 hours.
[0032] Secondly, the present application also provides a PB@GOx@ZIF-8 material prepared by the above method.
[0033] Again, the present application also provides a flexible electrode modified with PB@GOx@ZIF-8 material. The PB@GOx@ZIF-8 material prepared by the above method is dropped onto the working electrode of the screen-printed electrode, allowed to dry naturally at room temperature, and then a 0.5% Nafion solution is added to the surface for sealing, and the electrode is dried naturally at room temperature to obtain the flexible electrode.
[0034] Finally, the present application provides an application of the above-mentioned flexible electrode in a biosensor, wherein the biosensor is a portable sweat glucose sensor.
[0035] The portable sweat glucose sensor includes a sweat microfluidic channel, a flexible electrode modified with PB@GOx@ZIF-8 material, a circuit, and a wireless transmission and data collection device;
[0036] The sweat microflow channel includes a sweat collection channel, a reaction chamber, a sweat outflow channel, and sweat-absorbing paper. The flexible electrode modified with PB@GOx@ZIF-8 material is fixed to the reaction chamber. The reaction chamber is also equipped with a sweat outflow channel and sweat-absorbing paper.
[0037] The sweat collection channel, reaction chamber, and sweat outflow channel are all made of polydimethylsiloxane. Finally, the present invention also seeks protection for the use of the flexible electrode in a biosensor, which is a portable sweat glucose sensor.
[0038] Its beneficial effects are: the portable sweat glucose sensor can detect glucose in human sweat in real time and portably, thereby reflecting the changing trend of blood sugar in the human body. By detecting the change of current, it indirectly maps the change of blood glucose in the human body itself, thereby playing a role in monitoring and prevention, providing a convenient way for diabetic patients in their lives.
[0039] It can be seen from the above technical solution that, compared with the prior art, the present invention discloses a PB@GOx@ZIF-8 material and its preparation method and application in biosensors, which have the following beneficial effects:
[0040] The present invention successfully synthesized PB with a particle size of 50-200 nm and PB@GOx@ZIF-8 with a particle size of 300-800 nm. The sensitivity of the prepared PB@GOx@ZIF-8 biosensor for electrochemical detection of glucose can reach 10.617 μAmM. - 1 cm -2 The PB@GOx@ZIF-8 material maintained 55% of its original activity at 100°C and maintained its activity even after two months of storage. The sensor can detect glucose concentrations as low as 1 μM. Therefore, the sensor provides a simple and portable biosensing method for diabetic patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0042] Figure 1 SEM images of PB particles.
[0043] Figure 2 TEM image of PB particles.
[0044] Figure 3 TEM image of PB@GOx@ZIF-8 material.
[0045] Figure 4 High temperature performance test results diagram.
[0046] Figure 5 Enzyme activity test results diagram.
[0047] Figure 6 Schematic diagram of the microfluidic device.
[0048] Figure 7 Electrochemical test results.
[0049] Figure 8 Blood glucose test results using a commercial blood glucose meter. DETAILED DESCRIPTION
[0050] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0051] Preparation of PB particles
[0052] Example 1
[0053] Mix potassium ferrocyanide solution, potassium chloride solution and hydrochloric acid evenly and mark it as liquid A. The potassium ferrocyanide, potassium chloride and hydrogen chloride content in liquid A are 0.005 mol / L, 0.05 mol / L and 0.05 mol / L respectively.
[0054] Thoroughly mix the ferric chloride solution, potassium chloride solution, and hydrochloric acid, and mark it as solution B. Solution B contains 0.005 mol / L ferric chloride, 0.05 mol / L potassium chloride, and 0.05 mol / L hydrogen chloride.
[0055] Using a syringe pump, simultaneously titrate 20 mL of Solution A and 20 mL of Solution B into 100 mL of deionized water while stirring at room temperature at a rate of 200 μL / min. A blue solution is obtained. The solution is then centrifuged and washed until neutral at 11,000 rpm and dried at 65°C to obtain PB powder.
[0056] Example 2
[0057] Mix potassium ferrocyanide solution, potassium chloride solution and hydrochloric acid evenly and mark it as liquid A. The potassium ferrocyanide, potassium chloride and hydrogen chloride in liquid A are 0.01 mol / L, 0.1 mol / L and 0.1 mol / L respectively.
[0058] Thoroughly mix the ferric chloride solution, potassium chloride solution, and hydrochloric acid, and mark it as solution B. Solution B contains 0.01 mol / L ferric chloride, 0.1 mol / L potassium chloride, and 0.1 mol / L hydrogen chloride.
[0059] Using a syringe pump, simultaneously titrate 20 mL of Solution A and 20 mL of Solution B into 50 mL of deionized water while stirring at room temperature at a rate of 1000 μL / min. A blue solution is obtained. The solution is then centrifuged and washed until neutral at 5000 rpm and dried at 65°C to obtain PB powder.
[0060] Example 3
[0061] Mix potassium ferrocyanide solution, potassium chloride solution and hydrochloric acid evenly and mark it as liquid A. The potassium ferrocyanide, potassium chloride and hydrogen chloride content in liquid A are 0.005 mol / L, 0.05 mol / L and 0.05 mol / L respectively.
[0062] Thoroughly mix the ferric chloride solution, potassium chloride solution, and hydrochloric acid, and mark it as solution B. Solution B contains 0.005 mol / L ferric chloride, 0.05 mol / L potassium chloride, and 0.05 mol / L hydrogen chloride.
[0063] Using a syringe pump, simultaneously titrate 20 mL of Solution A and 20 mL of Solution B into 50 mL of deionized water while stirring at room temperature at a rate of 250 μL / min. A blue solution is obtained. This solution is then centrifuged and washed until neutral at 11,000 rpm and dried at 65°C to obtain PB powder.
[0064] SEM characterization of PB particles
[0065] The PB particles prepared in Example 1 were observed by scanning electron microscopy. Figure 1 The diameter of the PB particles is about 70nm, the structure of the particles is close to a perfect cube, and the surface is smooth, which meets the requirements of subsequent experiments in terms of structure and size.
[0066] TEM characterization of PB particles
[0067] The PB particles prepared in Example 1 were further observed by transmission electron microscopy. Figure 2 Among them, a) is the TEM image of PB particles, bd) is the elemental analysis image, it can be seen that the external structure of PB particles is relatively dense, the size structure is uniform, and Figure 2 The element distribution diagram in the figure shows that the N and Fe elements are evenly distributed, proving the synthesis of PB particles.
[0068] Preparation of PB@GOx@ZIF-8 materials
[0069] Example 4
[0070] The PB powder prepared in Example 1 was prepared into 100 μL of a 0.2 mg / mL PB solution, which was dissolved in 100 μL of a 5 mg / mL glucose oxidase solution and 0.649 g of 2-methylimidazole in 5 mL of an ethanol solution. The mixture was ultrasonically treated for 10 min and labeled as solution C, where the volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0071] 10 mg of zinc nitrate hexahydrate was dissolved in 5 mL of ethanol solution and sonicated for 10 min, which was labeled as solution D. The volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0072] Liquid C and liquid D were slowly mixed and reacted on a shaker for 20 minutes, and then centrifuged and washed at 5000 rpm until the supernatant was clear; the resulting precipitate was frozen in liquid nitrogen for 1 minute and then dried in a freeze-vacuum oven at -60°C for 24 hours to obtain PB@GOx@ZIF-8 material, which was stored at -20°C.
[0073] Examples 5-7
[0074] The amount of zinc nitrate hexahydrate in Example 4 was changed to 20 mg, 30 mg, and 40 mg, respectively. The experiment was repeated to prepare different PB@GOx@ZIF-8 materials, which were stored at -20°C.
[0075] Example 8
[0076] The PB powder prepared in Example 1 was prepared into 100 μL of a 0.2 mg / mL PB solution, which was dissolved in 100 μL of a 5 mg / mL glucose oxidase solution and 0.649 g of 2-methylimidazole in 5 mL of an ethanol solution. The mixture was ultrasonically treated for 10 min and labeled as solution C, where the volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0077] 10 mg of zinc nitrate hexahydrate was dissolved in 5 mL of ethanol solution and sonicated for 10 min, which was labeled as solution D. The volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0078] Liquid C and liquid D were slowly mixed and reacted on a shaker for 30 minutes, and then centrifuged and washed at 5000 rpm until the supernatant was clear; the resulting precipitate was frozen in liquid nitrogen for 1 minute, and then dried in a freeze-vacuum oven at -60°C for 24 hours to obtain PB@GOx@ZIF-8 material, which was stored at -20°C.
[0079] Examples 9-11
[0080] The amount of zinc nitrate hexahydrate in Example 8 was changed to 20 mg, 30 mg, and 40 mg, respectively. The experiment was repeated to prepare different PB@GOx@ZIF-8 materials, which were stored at -20°C.
[0081] Example 12
[0082] The PB powder prepared in Example 1 was prepared into 100 μL of a 0.2 mg / mL PB solution, which was dissolved in 100 μL of a 5 mg / mL glucose oxidase solution and 0.649 g of 2-methylimidazole in 5 mL of an ethanol solution. The mixture was ultrasonically treated for 10 min and labeled as solution C, where the volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0083] 10 mg of zinc nitrate hexahydrate was dissolved in 5 mL of ethanol solution and sonicated for 10 min, which was labeled as solution D. The volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0084] Liquid C and liquid D were slowly mixed and reacted on a shaker for 60 minutes, and then centrifuged and washed at 5000 rpm until the supernatant was clear; the resulting precipitate was frozen in liquid nitrogen for 1 minute and then dried in a freeze-vacuum oven at -60°C for 24 hours to obtain PB@GOx@ZIF-8 material, which was stored at -20°C.
[0085] Examples 13-15
[0086] The amount of zinc nitrate hexahydrate in Example 12 was changed to 20 mg, 30 mg, and 40 mg, respectively. The experiment was repeated to prepare different PB@GOx@ZIF-8 materials, which were stored at -20°C.
[0087] Example 16
[0088] The PB powder prepared in Example 1 was prepared into 100 μL of a 0.2 mg / mL PB solution, which was dissolved in 100 μL of a 5 mg / mL glucose oxidase solution and 0.649 g of 2-methylimidazole in 5 mL of an ethanol solution. The mixture was ultrasonically treated for 10 min and labeled as solution C, where the volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0089] 10 mg of zinc nitrate hexahydrate was dissolved in 5 mL of ethanol solution and sonicated for 10 min, which was labeled as solution D. The volume ratio of deionized water to anhydrous ethanol in the ethanol solution was 10:1.
[0090] Liquid C and liquid D were slowly mixed and reacted on a shaker for 24 hours, and then centrifuged and washed at 5000 rpm until the supernatant was clear; the resulting precipitate was frozen in liquid nitrogen for 1 minute and then dried in a freeze-vacuum oven at -60°C for 24 hours to obtain PB@GOx@ZIF-8 material, which was stored at -20°C.
[0091] Examples 17-19
[0092] The amount of zinc nitrate hexahydrate in Example 16 was changed to 20 mg, 30 mg, and 40 mg, respectively. The experiment was repeated to prepare different PB@GOx@ZIF-8 materials, which were stored at -20°C.
[0093] TEM characterization of PB@GOx@ZIF-8 materials
[0094] The PB@GOx@ZIF-8 material of Example 19 was characterized and analyzed by transmission electron microscopy. Figure 3 , where a) is the TEM image of PB@GOx@ZIF-8 material, and b) is the elemental analysis diagram. It can be seen that the Fe element in PB is distributed in ZIF-8, and the N and Zn elements are distributed throughout the entire ZIF material, indicating that PB nanoparticles are coated in the ZIF-8 material, which is consistent with the expected experimental results.
[0095] Comparative Example 1
[0096] Preparation of AgNWs@GOx@ZIF-8 materials
[0097] To 100 μL of the AgNWs solution and 100 μL of glucose oxidase (GOx, 5 mg / mL) solution, 0.649 g of 2-MI was added. After mixing, the mixture was added to 5 mL of deionized water and sonicated for 10 minutes. Next, 40 mg of zinc nitrate (Zn(NO3)2·6H2O) was added to the 5 mL solution and sonicated for 10 minutes. The solution was slowly mixed on a shaker for 24 hours. The resulting solution was centrifuged at 5000 rpm and washed several times in deionized water until the supernatant was clear. The resulting precipitate was frozen in liquid nitrogen for 1 minute and then dried under freeze-vacuum for 24 hours to obtain AgNWs@GOx@ZIF-8 powder. The powder was stored at -20°C.
[0098] Comparative Example 2
[0099] Preparation of AuNPs@GOx@ZIF-8 materials
[0100] To 100 μL of the AuNPs solution and 100 μL of the glucose oxidase (GOx, 5 mg / mL) solution, 0.649 g of 2-MI was added. The mixture was then added to 5 mL of deionized water and sonicated for 10 minutes. Next, 40 mg of nitric acid (Zn(NO₃)₂·6H₂O) was added to 5 mL of the mixed solution and sonicated for 10 minutes. The solution was slowly mixed on a shaker for 24 hours, centrifuged at 5000 rpm, and the precipitate was washed several times with deionized water until the supernatant became clear. The resulting precipitate was frozen in liquid nitrogen for 1 minute and then freeze-dried in a vacuum oven for 24 hours to obtain AuNPs@GOx@ZIF-8 powder. The powder was stored at -20°C.
[0101] High temperature performance testing
[0102] The products of Example 19, Comparative Example 1 and Comparative Example 2 were subjected to high temperature treatment at 80°C for 1.5h, and then enzyme activity kinetics absorption light detection was performed using a microplate reader. The results are as follows: Figure 4As shown, it can be seen that the PB@GOx@ZIF-8 material can ensure the activity of the internal GOx, and the absorption light energy reaches 0.55, while the absorption light data of AgNWs@GOx@ZIF-8 and AuNPs@GOx@ZIF-8 materials are at 0.1, proving that the PB@GOx@ZIF-8 material has high heat resistance.
[0103] Enzyme activity kinetics assay
[0104] The enzyme activity of PB@GOx@ZIF-8 and its centrifugal supernatant and GOx in Example 19 was tested. Figure 5 a. Calculation shows that the GOx loading rate in PB@GOx@ZIF-8 material can reach more than 85%, indicating that PB@GOx@ZIF-8 material has the ability to highly load GOx.
[0105] GOx and the PB@GOx@ZIF-8 material of Example 19 were treated at different temperatures to test their enzyme activities. The results are shown in Figure 5 bd (where Figure 5 b is GOx, Figure 5 c is PB@GOx@ZIF-8, Figure 5d is a comparison of GOx, PB@GOx@ZIF-8, and PB@ZIF-8. In the microplate reader data after 1.5 hours of high-temperature treatment, at room temperature, the kinetic absorbance data for glucose catalysis by PB@GOx@ZIF-8 accounted for 85% of the kinetic absorbance data for glucose catalysis by GOx. At 60°C, the absorbance of glucose catalysis by PB@GOx@ZIF-8 reached 80%, while that of glucose catalysis by GOx decreased to approximately 15%. Subsequently, at an increased temperature of 70°C, the absorbance of glucose catalysis by PB@GOx@ZIF-8 reached 70%, while that of glucose catalysis by GOx decreased to approximately 13%. At 80°C, the absorbance of glucose catalysis by PB@GOx@ZIF-8 still reached 65%, while that of glucose catalysis by GOx decreased to approximately 8%. At 90°C, the absorbance of glucose catalyzed by PB@GOx@ZIF-8 reached 60%, while that of GOx decreased to approximately 8%. At 100°C, the absorbance of glucose catalyzed by PB@GOx@ZIF-8 reached 55%, while that of GOx decreased to approximately 7%. This indicates that high-temperature treatment severely impacts the activity of GOx, resulting in a significant change in the kinetic absorbance values. After high-temperature treatment, GOx completely loses its catalytic activity, with the kinetic absorbance values dropping to a minimum or even disappearing. However, at temperatures of 70°C, 80°C, 90°C, and 100°C, the PB@GOx@ZIF-8 material still catalyzed the glucose catalysis. These experimental results demonstrate that GOx completely loses its catalytic activity under high-temperature treatment (above 70°C) and is unable to perform its function. Furthermore, the PB@GOx@ZIF-8 material maintains its catalytic activity even under high-temperature treatment (above 70°C), resolving the issue of GOx losing its catalytic activity at high temperatures.
[0106] The PB@GOx@ZIF-8 solution and GOx solution of Example 19 were stored at 39°C to simulate the normal ambient temperature. The enzyme activity test was then performed, and the results are shown in FIG. Figure 5e. It can be seen that even in the nearly two months of testing, the kinetic absorption light data of the PB@GOx@ZIF-8 material remains relatively stable. Compared with the GOx solution, the overall kinetic absorption light data of the PB@GOx@ZIF-8 material is higher. This is because the ZIF-8 shell acts as an exoskeleton to protect GOx. Under harsh environmental conditions, the PB@GOx@ZIF-8 material can still maintain catalytic activity. At the same time, the PB@GOx@ZIF-8 solution also shows long-term stability. Over a period of two months, the color development data of the PB@GOx@ZIF-8 material remained around 0.8-0.9, while the absorption light value of GOx decreased from between 0.6-0.7 to between 0.4-0.5, which proves that the PB@GOx@ZIF-8 material has long-term stability.
[0107] Example 20
[0108] Flexible electrode preparation
[0109] The flexible electrode is a screen-printed electrode, consisting of a counter electrode, a working electrode, and a reference electrode. The reference electrode is a silver electrode, and the counter electrode and the working electrode are composed of carbon electrodes. The PB@GOx@ZIF-8 material prepared in Example 19 is dropped onto the working electrode and naturally dried at 39°C; then a 0.5% Nafion solution is added to the surface to seal the layer, and the mixture is naturally dried at room temperature.
[0110] Example 21
[0111] Preparation of portable sweat glucose sensor
[0112] The portable sweat glucose sensor includes a sweat microfluidic channel, a flexible electrode modified with PB@GOx@ZIF-8 material, a circuit, and a wireless transmission and data collection device;
[0113] Sweat micro-flow channel Figure 6 , including a sweat collection channel, a reaction chamber, a sweat outflow channel and sweat absorbing paper; the flexible electrode modified with PB@GOx@ZIF-8 material is fixed to the reaction chamber part; and the reaction chamber part is provided with a sweat outflow channel and sweat absorbing paper;
[0114] The sweat collection channel, reaction chamber, and sweat outflow channel are all made of polydimethylsiloxane.
[0115] Electrochemical testing
[0116] The electrochemical test results are shown in Figure 7, where a is the kinetic curve of electrochemical detection of glucose; b is the standard curve for detecting glucose; As can be seen from the figure, the PB@GOx@ZIF-8 sensor shows good detection linearity for different concentrations of glucose. As the glucose concentration gradually increases, the reduction current of PB@GOx@ZIF-8 shows a gradually increasing trend. In the experiment, the minimum detection limit of the PB@GOx@ZIF-8 sensor for glucose concentration is 1μM, which makes it possible to detect glucose in human sweat. The sensitivity of the chronoamperometric detection is 10.617μA / (mM·cm 2 To demonstrate the stability of the sensor, multiple chronoamperometric detection experiments were performed, and the results showed a correlation coefficient of 0.9897. The excellent catalytic activity of the material can be attributed to the following reasons: (1) the suitable mesoporous structure of ZIF-8 can capture more glucose, promote the diffusion of substrate / product molecules and electron transport; (2) ZIF-8 has a good adsorption capacity for GOx, which enables it to maintain the conformational freedom of the enzyme molecule in the spacious environment of ZIF-8, which is conducive to maintaining its biological activity.
[0117] Healthy volunteers with no history of diabetes were selected as research subjects and their sweat glucose levels were tested. Figure 7 c is a schematic diagram of the glucose sensor patch test, as well as the electrodes and a commercial finger-pricking blood glucose meter for blood glucose testing. Volunteers exercised on a treadmill for 30 minutes and then rested for 30-60 minutes. As the volunteers continued to sweat, the current value in the 0-60 minute period also changed. The glucose content was detected to fluctuate within the range of 80μM-105μM. The results are shown in Figure 7 d. At the same time, as a comparison, a commercial blood glucose meter was used to collect blood from volunteers every 15 minutes for a total of 5 sets of data. The results are shown in Figure 8 The data from commercial blood glucose meters fluctuated within the range of 4.0-6.0 mM. The study found that the sweat glucose concentration detected by the PB@GOx@ZIF-8 flexible electrode had a good correlation with the results of human blood glucose detection using a commercial blood glucose meter.
[0118] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing PB@GOx@ZIF-8 material, characterized in that: The specific steps include: S1, Preparation of PB particles Mix potassium ferrocyanide solution, potassium chloride solution and hydrochloric acid evenly and mark it as solution A; Thoroughly mix the ferric chloride solution, potassium chloride solution, and hydrochloric acid and mark it as solution B; Use a microsyringe pump to simultaneously add solution A and solution B to deionized water and continue stirring at room temperature. After the titration is completed, a blue solution of PB is obtained. Then, centrifuge and wash until neutral, and dry to obtain PB powder. S2, Preparation of PB@GOx@ZIF-8 Materials Prepare PB solution, mix it with glucose oxidase solution, 2-methylimidazole, and ethanol solution, and perform ultrasonic treatment to obtain solution C; Dissolve zinc nitrate hexahydrate in ethanol solution and ultrasonicate to obtain solution D; Finally, liquid C and liquid D were slowly mixed and reacted on a shaker, centrifuged and washed, and the resulting precipitate was frozen in liquid nitrogen and dried in a freeze dryer to obtain PB@GOx@ZIF-8 material, which was stored at -20°C for future use.
2. The method for preparing a PB@GOx@ZIF-8 material according to claim 1, characterized in that: In step S1, the concentration of potassium ferrocyanide in solution A is required to be 0.001-0.1 mol / L, the concentration of potassium chloride is required to be 0.01-1 mol / L, and the concentration of hydrochloric acid is required to be 0.01-1 mol / L; The concentration of ferric chloride in solution B is required to be 0.001~0.1 mol / L, the concentration of potassium chloride is required to be 0.01~1 mol / L, and the concentration of hydrochloric acid is required to be 0.01~1 mol / L.
3. The method for preparing a PB@GOx@ZIF-8 material according to claim 1, wherein In the titration of step S1, the volume ratio of solution A, solution B, and deionized water is 1:1:2.5-50; Titration speed is 100-1000 μL / min; The rotation speed of the centrifugal washing is 5000-15000 rpm; The drying temperature is 65°C.
4. The method for preparing a PB@GOx@ZIF-8 material according to claim 1, characterized in that: In step S2, when preparing solution C, the concentration of the PB solution is 0.1 to 5 mg / mL, and the amount used is 50 to 500 μL; the concentration of the glucose oxidase solution is 1 to 10 mg / mL, and the amount used is 50 to 200 μL; the amount of 2-methylimidazole is 0.5 to 2 g; the ethanol solution is prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 5 to 20:1, and the amount used is 5 to 20 mL; and the ultrasonic treatment time is 5 to 30 min.
5. The method for preparing a PB@GOx@ZIF-8 material according to claim 1, characterized in that: In step S2, when preparing solution D, the amount of zinc nitrate hexahydrate used is 10-40 mg, the ethanol solution is a mixed solution of deionized water and anhydrous ethanol, mixed in a volume ratio of 5-20:1, and the amount used is 5-20 mL; the ultrasonic treatment time is 5-10 min.
6. The method for preparing a PB@GOx@ZIF-8 material according to claim 1, characterized in that: In step S2, solution C and solution D are slowly mixed on a shaker for a reaction time of 20 to 1440 minutes; The rotation speed of the centrifugal washing is 2000-8000 rpm; The liquid nitrogen freezing time is 1 to 10 minutes; The temperature of the freeze dryer is -60°C and the time is 12 to 48 hours.
7. A PB@GOx@ZIF-8 material prepared by the method according to any one of claims 1 to 6.
8. A flexible electrode modified with PB@GOx@ZIF-8 material, characterized in that: The PB@GOx@ZIF-8 material prepared by the method according to any one of claims 1 to 6 is dropped onto the working electrode of the screen-printed electrode, allowed to dry naturally at room temperature, and then a 0.5% Nafion solution is added to the surface for sealing, and allowed to dry naturally at room temperature to obtain the flexible electrode.
9. Use of the flexible electrode according to claim 8 in a biosensor, characterized in that: The biosensor is a portable sweat glucose sensor.
10. The use according to claim 9, characterized in that The portable sweat glucose sensor includes a sweat microfluidic channel, a flexible electrode modified with PB@GOx@ZIF-8 material, a circuit, and a wireless transmission and data collection device; The sweat micro-flow channel includes a sweat collection channel, a reaction chamber, a sweat outflow channel and sweat absorbing paper; The flexible electrode modified with PB@GOx@ZIF-8 material is fixed to the reaction chamber, and the reaction chamber is provided with a sweat outflow channel and sweat-absorbing paper. The sweat collection channel, reaction chamber, and sweat outflow channel are all made of polydimethylsiloxane.